2017
DOI: 10.1002/ajoc.201700477
|View full text |Cite
|
Sign up to set email alerts
|

1(3)‐Formyl‐β‐carbolines: Potential Aldo‐X Precursors for the Synthesis of β‐Carboline‐Based Molecular Architectures

Abstract: b-Carboline, ap rivileged scaffold in the alkaloid family,h as ab road spectrum of medicinal properties and is found in severalc ommercial drugs, such as tadalafil, cipargamin, anda becarnil. Owing to the immense pharmacological importance of b-carboline derivatives, their synthesis has been one of the frontier areas of research in recent years. In this context,1 (3)-formyl-9H-b-carbolines are promising "aldo-X" bifunctional building blocks (AXB3s) that offer alternate avenues for the diversity-oriented synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 142 publications
0
25
0
Order By: Relevance
“…[ 29 ] In particular, substituted 4‐iodopyrazole‐3/5‐carbaldehydes, which can be easily prepared, are attractive moieties to install desired pattern. Recently, our group comprehensively summarized the synthesis and applications of aldo‐x precursors like 4‐formyl‐1 H ‐pyrazole‐3‐carboxylate [ 30 ] and 9 H‐ pyrido[3,4‐ b ]indole‐1‐carbaldehyde [ 31 ] (Figure 5).…”
Section: Introductionmentioning
confidence: 99%
“…[ 29 ] In particular, substituted 4‐iodopyrazole‐3/5‐carbaldehydes, which can be easily prepared, are attractive moieties to install desired pattern. Recently, our group comprehensively summarized the synthesis and applications of aldo‐x precursors like 4‐formyl‐1 H ‐pyrazole‐3‐carboxylate [ 30 ] and 9 H‐ pyrido[3,4‐ b ]indole‐1‐carbaldehyde [ 31 ] (Figure 5).…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of substituted 9H-pyrido [3,4-b]indole-3-carbaldehydes (5a-j) was accomplished via modification in the previously documented procedures (Scheme 3). [15,17] Another precursor, the substituted cinnamyl bromides (AÀH) were readily prepared in high yields (80-95%) from Morita-Baylis-Hillman adducts via bromination with PBr 3 at 0 o C (SI). [18] In order to achieve the synthesis of desired b-carboline C-3 coupled butyrolactones, the optimization studies were performed using 1-(4-bromophenyl)-9H-pyrido [3,4-b]indole-3-carbaldehyde (5b) and cinnamyl bromide (A) as the model substrates.…”
Section: Resultsmentioning
confidence: 99%
“…[14] More recently, our group reviewed the synthetic and medicinal developments of b-carboline C-1(3) tethered and fused frameworks which showed that diastereoselective synthesis of bcarboline C-3 tethered a-methylene g-butyrolactones remain unprecedented in literature. [15] A retrosynthetic analysis of the designed molecular hybrid revealed that prototype-I may be constructed via tandem approach by in situ intramolecular lactonisation of homoallyl alcohols (II) afforded via Barbier-Type allylation of 3-formyl bcarboline (III) and substituted allyl bromides (IV) as depicted in Scheme 2. Accordingly, efforts were directed to develop a domino approach for the facile synthesis of designed molecular hybrids via the application of indium-mediated Barbier-Type reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Devi et al. has given a comprehensive report which highlights the importance of 1‐formyl‐β‐carbolines and 3‐formyl‐β‐carbolines for the synthesis of β‐carboline‐based molecular frameworks and their medicinal potential . As depicted in Scheme , N ‐subsituted Methyl 1‐formyl‐9H‐β‐carboline‐3‐carboxylate 10 were synthesized using Pictet‐Spengler reaction of L ‐tryptophan methyl ester with 1,1‐dimethoxy acetaldehyde using TFA as a catalyst to afford adduct 8 , which was further aromatized and deprotected using KMnO 4 and refluxing AcOH/H 2 O (2:3), respectively to generate compound 9 .…”
Section: β‐Carboline Fused Heterocycles Synthesized Via Post‐pictet‐smentioning
confidence: 99%